Fluoride Concentration Modelling in Konya City Drinking Water Wells via Geographical Information System - DURSUN, SUKRU; SAVAS DURDURAN, S.; KUNT, FATMA (Asian Journal of Chemistry, 2010)
Fluoride is one of the important elements in drinking water. This element is needed in small quantities; because it has an important role for health. Even small quantities of some trace elements have significant effect on human health. In this study, bearing in mind that especially excessive or low fluoride content of drinking waters is important for human health, water samples were collected from 50 different water wells in Konya city centre for determination of their fluoride concentrations. Water fluoride data analyses for modelling were carried out using Geographical Information System (GIS) then, fluoride level maps were presented to aid the identification of areas where high-fluoride waters and fluorosis may be a problem. It was observed that fluoride levels of all collected samples were below the limit given in T.S.-266 and WHO standards. The highest fluoride concentration was detected in water wells at Sakarya area with 0.42 mg L-1. The lowest fluoride level was obtained from Ali Tasoluk well water with 0.092 mg L-1. Fluoride level in the tap water has a great importance for tooth and bone health. In the systems where water is supplied from wells with low fluoride content, it is necessary addition of fluoride using appropriate methods. In addition, if it is not possible for fluoride addition, it is necessary to inform the people who using this water about application fluoride tablets.